Treatment of acute pandysautonomia with intravenous immunoglobulin. - Mericle, R A (1997)
Acute pandysautonomia has been suggested to be an uncommon variant of Guillain-Barre syndrome. Acute pandysautonomia does not seem to have been treated with intravenous immunoglobulin or other therapies proved efficacious in Guillain-Barre syndrome. A patient is reported with severe acute pandysautonomia who responded dramatically to intravenous immunoglobulin. The findings are consistent with a dysimmune pathogenesis for this syndrome and suggest a possible treatment for future cases.